PENGARUH WHISTLEBLOWING SYSTEM, KOMITE AUDIT, DAN AUDIT INTERNAL TERHADAP PENCEGAHAN FRAUD PADA DUNIA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024 - Manurung, Siska; Dewi Astuti, Tutut (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to explore the impact of whistleblowing systems, audit committees, and internal audits in preventing fraud in banking institutions listed on the IDX from 2022 to 2024. The method applied is quantitative by utilizing secondary data from the annual reports of 24 banks and hypothesis testing using multiple linear regression analysis. The whistleblowing system is measured by comparing the number of violation reports with the total items according to the KNKG, while the audit committee is measured based on the percentage of members who have a background in accounting or finance, and internal audit is assessed based on the qualifications of the head of the internal audit division. The results of the t-test showed that the whistleblowing system, audit committee, and internal audit each had a significant positive influence on fraud prevention efforts, which means that strengthening each mechanism could increase the effectiveness of controlling fraud. The F test also indicates that the three variables simultaneously have a significant effect on fraud prevention, indicating that the integration of the three creates a multi-layered supervisory system that improves integrity and stability in the banking sector. These findings reinforce the relevance of Agency Theory and Fraud Triangle Theory, where strict supervision and an efficient whistleblowing system can reduce opportunities and opportunistic behavior of fraudsters.